The Impact of Quality Management on Employees' Job Satisfaction in Respiratory Intensive Care Unit at Labbafinejad Hospital (Tehran University of Medical Sciences, 2016)
Background: Quality management as an organizational strategy helps enhance hospital efficiency, effectiveness and productivity. This study aimed to examine the impact of quality management on employees' job satisfaction at Respiratory Intensive Care unit, Labafijejad Hospital. Materials and Methods: A participatory action research was used for the intervention in 2013. A quality improvement team was established and operational processes were improved using a quality management model. The quality improvement team identified and standardized working processes, identified quality goals for the processes and improved them until achieved quality goals. Employees' job satisfaction data was collected before and after the intervention. Results: The quality management model implementation improved employees' job satisfaction at the Respiratory Intensive Care unit. Employees' job satisfaction was increased from 56.6 percent in 2013 to 68.3 percent in 2014. Integrating employees' needs in quality improvement activities helps sustain the benefits of quality management. As a result, employees' moral and satisfaction increase. Conclusions: Implementing an appropriate quality management model appropriately in a supportive environment helps enhance employees' job satisfaction and morale. Managerschr('39') and employeeschr('39') commitment and involvement in quality improvement activities are required for successful quality management implementation.